(untitled) (CR. Conservación y Restauración, 2025)
The illicit trafficking of cultural property is an international issue that concerns not only public institutions but society in general, regardless of the use and safeguarding of cultural heritage, so generating prevention actions around it has an impact on a culture of prevention. For this reason, the Coordinación Nacional de Conservación del Patrimonio Cultural (CNCPC) of the Instituto Nacional de Antropología e Historia (INAH) developed a project to establish a permanent program for preventive conservation and prevention of illicit trafficking of cultural property. This text presents a general overview of the most relevant actions that have been developed in the three main lines of action, previously campaigns, which are linked to each other, with the intention of disseminating the work carried out between 2020 and 2023, with special attention to outreach activities, training, and regulations.